Celeste Holm syndrome on character actors from Hollywood's golden age - Lazar, David 1957- (University of Nebraska Press, 2020)
""Celeste Holm Syndrome" is a series of essays about character actors in Hollywood cinema"--
Keywords: Motion picture actors and actresses / United States / Biography; Characters and characteristics in motion pictures; Motion picture actors and actresses; United States; Biographies